How can the implementation of children's literature support the literacy development in a group of first graders at Institución Educativa San Juan Bosco? (2018)
ABSTRACT: This action research project was done to improve literacy development in 1st graders students through the use of childrens literature as a method to promote Spanish and English writing. The project was carried out at Institución educativa San Juan Bosco during two school terms in a first grade. Data was gathered through a focal group, an interview and a reflective journal; these ones were triangulated and analyzed afterwards. Findings revealed that the use of Childrens literature not only promoted the development of literacy, but also fostered the participation, the imagination and the recognition of meaning through images.